DESAIN INSTRUMEN TES KEMAMPUAN PEMECAHAN MASALAH MATEMATIS BERBASIS GAME UNITY - Kurniawan, Riqi; Lukman, Hamidah Suryani; Nurcahyono, Novi Andri (Pendidikan Matematika UNIMOR, 2021)
This study aims to find out the process of designing test instruments and produce instrument design test mathematical problem-solving ability based on game unity. The research method used is Research and Development by using the Addie model. ADDIE stage used is analyze and Design. The analysis is carried out by the stages of problem formulation, collecting data, evaluating data feasibility, analyzing and interpreting relevant data, and organizing and presenting results that are then obtained compared to current issues, while the design is done by making hypothetical designs, then developed into a display design using the software. The results obtained are the process of designing instrument test mathematical problem-solving ability based on game unity can be designed with the stages of searching for valid mathematical problem-solving ability test or create a problem that is then validated, flowchart creation, design, and application creation using game engine unity. Test instrument design is made using a unity game engine, problem presentation is made in the form of images and instructions, and filling answers using ideal problem-solving stages.